Destination Personality, Satisfaction, And Tourist Future Behavior: The Case Of North Cyprus - Rostampour, Mehrnoush (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Going through application of destination personality in North Cyprus and finding about the essence of its relation to tourist satisfaction, and tourist behavior, considering the moderating effect of tourist motivation on relation between destination personality and tourist satisfaction as the main aim of this study. This study focused on two aims: 1) the relationship between destination personality adopted from Aaker (1997) personality scale in tourism realm _ North Cyprus_ due to tourist feeling of satisfaction and consequently their intention to revisit North Cyprus as a destination and also their intention to recommend it to others which is illustrator of tourist future behavior, 2) how tourists’ motivation factors as a moderator affect the relationship between destination personality in relation with tourist feeling of satisfaction. The study shows that there is no direct and significant relationship between destination personality and tourist’s satisfaction. The reason may be rooted in what Ye (2012) during his study claimed that since the personality traits of Aaker (1997) brand personality scale is peculiar for business section it is probable and possible that not all of those traits be significant and sensible in tourism and destination dimension. Regarding the intention of tourist to recommend and revisit the destination is affected significantly and directly by tourist’s satisfaction. So destination personality according to anthropomorphism theory and the sense and the tie created between tourist and destination leads in attracting more tourists. Keywords: Destination Personality, Tourist Future Behavior, North Cyprus. ………………………………………………………………………………………………………………………… ÖZ: Çalışmanın temel amacını; KKTC’nin destinasyon kişiliğinin ve turist tatmini,davranışı ile olan ilişkisini ve turist motivasyonunun destinasyon kişiliği ve turist tatminindeki aracı etkisinin ortaya konması oluşturmuştur. Çalışma temel olarak iki amacı hedeflemiştir. Bunlardan ilki; Aaker ‘a ait (1997) destinasyon kişiliği ölçeğinin turizmde ve bir destinasyon olarak KKTC’de uygulanması ve turist tatmini ve ileriye dönük turist davranışlarına etkisinin ortaya konmasıdır. Çalışmanın bir diğer amacı ise turist motivasyonunun destinasyon kişiliği ve tatmini arasındaki aracı rolünün ortaya konmasıdır. Çalışmanın sonuçlarına göre destinasyon kişiliği ile turist tatmini arasında doğrudan bir ilişki yoktur. Bu sonuc literatürdeki çalışmalarda (Ye, 2012) söz konusu ölçeğin işletme alanına uygunken turizm ve özellikle de destinasyonlara uyarlanmasının çokda anlamlı olmayabileceğini desteklemektedir. Çalışmanın bir diğer sonucu ise gelinen destinasyonu ilerde tavsiye etme ve tekrar ziyaret etmenın turist tatmini ile doğrudan ve anlamlı ilişkisi olduğudur. Dolayısıyla antromorfozyum kuramıylada paralel olarak destinasyon kişiliğinin kanalıyla turist ve destinasyon arasında kurulucak bağın turist akışını pozitif yönde etkileyebileceğini desteklemektedir.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2013. Supervisor: Assist. Prof. Dr. Rüçhan Kayaman.
Keywords: Tourism; Tourism - Cyprus, North; Destination Personality, Tourist Future Behavior, North Cyprus